Towards an interpretation of the first measurements of energy correlators in the quark-gluon plasma - Carlota Andres; Fabio Dominguez; Jack Holguin; Cyrille Marquet; Ian Moult (Journal of High Energy Physics)
Abstract Energy correlators have recently been proposed as a class of jet substructure observables that directly link experimental measurements of the asymptotic energy flux with the field theoretic description of the underlying microscopic dynamics. This link holds particular promise in heavy-ion physics, where both experimental measurements and theoretical interpretations are inherently complex. With recent measurements of energy correlators in proton-proton collisions, the first measurement of these observables on inclusive jets in heavy-ion collisions underscores the importance of a theoretical understanding of their behavior in this complex environment. In this manuscript, we extend our previous calculations to account for several effects necessary for a qualitative understanding of the behavior of energy correlators on inclusive jets in heavy-ion collisions. Through a semi-analytic approach implemented in a hydrodynamically expanding quark-gluon plasma (QGP), we account for medium-induced radiation with leading broadening effects, selection biases arising from energy loss, and a description of the confinement transition. Our results represent a crucial first step towards interpreting the measurements of energy correlators on inclusive jets in heavy-ion collisions, which marks a significant milestone in connecting heavy-ion experiment and fundamental quantum field theory, in the quest to disentangle the microscopic dynamics of the QGP.